The Influence Of Transformational Leadership And Motivation On Employee Performance In Coffeehouse Business - Abdillah, Afif; Pradana, Bayu Ilham (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of organizational culture and interpersonal communication on employee performance in XYZ company operating in the oil and gas industry. Design/Methodology/Approach – This study employs an associative quantitative research approach. Data were collected through a Likert-scale questionnaire from 66 employees selected using convenience sampling from a population of 152 employees. The data were analyzed using SPSS through validity, reliability, classical assumption, multiple linear regression, and hypothesis testing to examine both partial and simultaneous relationships among the variables. Findings – The results show that organizational culture has a positive and significant effect on employee performance, both partially and simultaneously. Meanwhile, interpersonal communication does not demonstrate a significant partial or simultaneous effect on employee performance. However, when organizational culture and interpersonal communication are examined together, both variables show a positive influence on employee performance. These findings indicate that strengthening organizational culture is a key factor in improving employee effectiveness within high-risk industrial environments.   Originality/Value This research is original in simultaneously examining organizational culture and interpersonal communication within an oil and gas company context. The findings provide practical value by clarifying which internal factors should be prioritized to enhance employee performance.